Упрощенный метод анализа цепочечного соединения СВЧ-четырехполюсников - Glushchenko, E. N. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
A simplified method for determining the parameters of a chain connection of microwave four‑ports is described. The method is based on electronic circuit analysis, modified for ultra‑high frequencies. The operating parameters of such a connection are obtained analytically, without using the traditional matrix theory apparatus, directly from the Y‑ or Z‑parameters of the circuit elements.